Qasmūna bint Isma'il bin Bagdalla al-Yahūdi: frammenti di poesia araba andalusa secondo le fonti arabe (Altre Modernità, 2014)
The Jewish Woman Poetry in the middle-age not represent a field of study in itself because most of the evidences of women literary production had not been part of Jewish Literary Heritage. Considerable exeption, Islam represent a context in wich woman writings have been not only transmitted but also seen as a part of the literary tradition. Relating largerly upon two literary sources, the Nuzhat al-julasâ' fî ash'âr al-nisâ of Suyûti (1445-1505) and the Nafh al Tîb min ghsn al-Andalus of al-Maqqari (1578-1632) this article would like to focalise the poetical production in classical arabic of Qasmûna Bint Ismâ'îl bin Baghdalla al-Yahûdi, one of the very few Jewish Poetess lived in al- Andalus between XI-XII century. Both the sources quotes the Rayât al-mubarrizin wa-ghayât al-mumayyzîn, the Geographical, Historical and Literary work of the famous Andalusian Historian Alî Ibn Mûsa Ibn Sa'îd al Magribi al-Andalusi (1213-1286) manuscript in a large part losted.Aim is to focus the poetical production of Qasmûna Bint Ismâ'îl al Yahûdi and his transmission through Arabic Anthologies dedicated to the Arabic Literary Tradition in al-Andalus and Islam. More than her religious belonging to Islam as a religion, the main reason for the transmission of Qasmûna's collection of poems seem to be the language and the style of composition, as well as her andalusian origins. For the nature of relations between Jewish communities and Islam in the Middle Ages, arabic historiographical sources become a cross-cultural narrative setting for Jewish and Islamic History, and their study fundamental in order grasp the develop of Jewish Thought in Middle Ages.